Publicystyka Wacława Nałkowskiego przeciwko Litwosowi - perspektywa retoryczna = Wacław Nałkowski`s journalism against Litwos - rhetorical perspective - Hawrysz, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of interest of this study is a journalistic series of critical speeches by Wacław Nałkowski, an outstanding Polish geographer, educator and social activist. The articles were directed against Henryk Sienkiewicz and his work, however, not from an artistic perspective, but from an ideological, socio-political one. In this cycle, traces of rhetorical art are clearly visible - both at the structural level and in the area of linguistic shape. The aim of the analysis is to indicate and describe the elements of "dispositio" and "elocutio" present in the series of articles by W. Nałkowski, which will also reveal the rhetorical foundations of contemporary journalism.
Keywords: publicystyka; Sienkiewicz, Henryk (1846-1916); Nałkowski, Wacław (1851-1911); retoryka; dispositio; elocutio; rhetoric; journalism; 19-20 w.